MAGNETIC SUSCEPTIBILITY AND HEAVY METALS SOIL ACCUMULATION IN UKRAINIAN URBAN AREAS - Menshov, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Soil pollution is an aspect of environmental magnetism research. The main objects are heavy metals and other chemical compounds. They pollute the environment and are dangerous for human life. Purpose. The magnetic properties of polluted soils investigation for different technogenic sources and impact on the territory. Methodology. The field stage work includes ecological and soil research, measuring the volume magnetic susceptibility with field kappameters. Laboratory studies include measuring mass-specific magnetic susceptibility with kappameters AGICO, MS-2, magnetization measurements, measuring magnetic parameters of the hysteresis loop with rock generator and special magnetometer equipment, determination of elemental composition, and electron magnetic microscopy. Findings. Magnetic susceptibility of polluted soils ("urbanozems") increases in the upper humus horizons (A). New magnetic particles (PM particles) tend to form during high-temperature processes. There was found a high correlation between magnetic susceptibility and the lead, zinc, and copper content in the polluted soils. Originality. A correlation between magnetic susceptibility and soil pollutants has been described. Heavy metals often stick to the surface of ferromagnetic materials and penetrate the structure of the crystal lattice under high-technology processes, with these compounds accumulating in soils. Practical value. Further research into soil magnetism informative value is associated with the development of an optimal soil mapping technology in urban areas. Environmental magnetic investigation is a low-cost and high-performance technology to assess the technogenic and anthropogenic impact on the environment.